If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2s+65=4s+33
We simplify the equation to the form, which is simple to understand
2s+65=4s+33
We move all terms containing s to the left and all other terms to the right.
+2s-4s=+33-65
We simplify left and right side of the equation.
-2s=-32
We divide both sides of the equation by -2 to get s.
s=16
| 3+x/6=-4 | | 3(x+117)=201 | | -7x-15=20 | | 2x^4= | | -32x-37+195=-57-83x | | -4g+10g=120 | | 15=8-6 | | 3u-2(2u-7)=2(3+u)-4 | | -1.2=-x/5 | | -8x-2y=40 | | -124=4w | | 5x+5.4=3x+9.6 | | 2(a+3)=15 | | 16*4= | | 11x^2+x-10=0 | | x/25=-3 | | -58b-166=41-49b+27 | | 4x+11=36 | | 75=9-s | | 4x+5.4=2x+9.6 | | 0=x^3-6x^2+12x-8 | | 2x^2-3x=2 | | 7x+4-6x=20 | | 11+w=-45 | | -3=12x+8-13x | | ln(4x-7)+ln(2x)=2ln(x) | | 19=a+5 | | 9x+6x-12x=-7x+2-12+5x | | 29x-7-17x=3(4x-3)+2 | | 3c= | | 11-9(x+3)-5=11+3(9-3x)-81 | | 11-9(x+3)-5=11+3(9-3x)-81 |